Clinical features of childhood granulomatosis with polyangiitis (wegener’s granulomatosis) - Marek Böhm; María Isabel González; Seza Özen; Angela Pistorio; Pavla Doležalová; Paul Brogan; Giancarlo Barbano; Claudia Sengler; Marisa Klein‐Gitelman; Pierre Quartier; Anders Fasth; Troels Herlin; et al. (2014)
BACKGROUND: Granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis (WG), belongs to the group of ANCA-associated necrotizing vasculitides. This study describes the clinical picture of the disease in a large cohort of GPA paediatric patients. Children with age at diagnosis ≤ 18 years, fulfilling the EULAR/PRINTO/PRES GPA/WG classification criteria were extracted from the PRINTO vasculitis database. The clinical signs/symptoms and laboratory features were analysed before or at the time of diagnosis and at least 3 months thereafter and compared with other paediatric and adult case series (>50 patients) derived from the literature. FINDINGS: The 56 children with GPA/WG were predominantly females (68%) and Caucasians (82%) with a median age at disease onset of 11.7 years, and a median delay in diagnosis of 4.2 months. The most frequent organ systems involved before/at the time of diagnosis were ears, nose, throat (91%), constitutional (malaise, fever, weight loss) (89%), respiratory (79%), mucosa and skin (64%), musculoskeletal (59%), and eye (35%), 67% were ANCA-PR3 positive, while haematuria/proteinuria was present in > 50% of the children. In adult series, the frequency of female involvement ranged from 29% to 50% with lower frequencies of constitutional (fever, weight loss), ears, nose, throat (oral/nasal ulceration, otitis/aural discharge), respiratory (tracheal/endobronchial stenosis/obstruction), laboratory involvement and higher frequency of conductive hearing loss than in this paediatric series. CONCLUSIONS: Paediatric patients compared to adults with GPA/WG have similar pattern of clinical manifestations but different frequencies of organ involvement.